Legally blonde - Smith, Kirsten 1970-; McCullah Lutz, Karen; Kent, Rolfe 1963- (Sony Pictures Home Entertainment, 2006)
"She's a Beverly Hills beauty who will do anything to keep her man. Even if it means going all the way - to law school. Elle Woods is a California blonde with couture clothes, fabulous friends and the hottest boyfriend on campus. So when Warner Huntington III suddenly dumps her and heads for Harvard Law School, Elle takes matters into her own perfectly manicured hands. She enrolls too"--Container insert
Special features: deleted scenes; featurettes: "Inside Legally blonde" and "The hair that ate Hollywood"; music video "Perfect day" by Hoku original theatrical trailer; trivia track; 2 audio commentaries featuring Robert Luketic, Reese Witherspoon, Marc Platt & the film crew
Spielfilm, Orig., USA: 2001
Keywords: Gerichtsfilm; Liebesfilm; Serienfilm; Filmkomödie; Harvard Law School / Comedy; Harvard Law School / Drama; Women law students / Drama; Women college students / Drama; Video recordings for the hearing impaired; Harvard Law School; Women college students; Women law students; Comedy; Romantic comedy films; Feature films; Comedy films; Feature films / United States; Drama; Fiction films; Films comiques; Vidéos pour personnes handicapées auditives; Films de fiction; Film; DVD-Video